Analisis Efektifivitas Pendapatan Asli Daerah Dalam Menilai Kinerja Badan Pengelolaan Keuangan Dan Pendapatan Daerah Kabupaten Bolaang Mongondow Selatan - Rusdi, Wahyudi; Aliu, Revaldi (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2021)
The purpose of this study was to determine the Financial Performance of South Bolaang Mongondow Regency (Bolsel) through an analysis of the effectiveness of PAD. The object of the research is the Regional Finance and Revenue Management Agency (BPKPD) of South Bolaang Mongondow Regency. The data used is secondary data from the 2017-2020 budget realization report. The data analysis technique is descriptive quantitative analysis. The results showed that the analysis of the effectiveness of PAD at the BPKPD of South Bolaang Mongondow Regency in 2017 and 2018 was quite effective, then increased to very effective in 2019 and 2020. For Trend analysis in the next 5 years, the results tend to increase, this is a very good implementation of performance. South Bolaang Mongondow Regency.